Educating for collaborative practice: an interpretation of current achievements and thoughts for future directions. Issue 1 (6th October 2017) - Hudson, Judith Nicky; Croker, Anne
Abstract : Context: The Edinburgh Declaration, developed in 1998 as a pledge to alter the character of medical education to more effectively meet the needs of society, included a recommendation to increase the opportunity for joint learning between health and health‐related professions, as part of the training for teamwork. This article acknowledges achievements since the Declaration in relation to this recommendation, using an umbrella term for the phenomenon, 'educating for collaborative practice', and presents a perspective framed as a series of questions to encourage reflection on future directions. Methods: A literature interpretation, informed by philosophical hermeneutics, was conducted using text sets comprising reports and reviews from a section of the international literature since 1988. The interpretation involved: engaging with meanings as presented in the chosen texts; making iterative returns to the texts to explore emerging understanding; and ensuring parts of our understanding from particular texts were fused with complete understanding of the texts as a whole. A lens of appreciative inquiry facilitated acknowledgement of what has been achieved, while being curious about how it could be. Results: Interpretation of the selected literature revealed notable achievements. Areas for further consideration were identified in relation to three themes: establishing shared understanding AND purpose behind use of terminology; being a conduit AND sharing responsibility for change; exploring ways of doing things AND ensuring ongoing inclusivity. Conclusions: Interpreting the current literature on 'educating for collaborative practice' has generated questions for reflection on how it may be otherwise. Readers are encouraged to embrace the tensions inherent in unanswered questions, providing space for communication, initiative and diversity of thought. An ongoing dialogue with the literature is proposed, asking whether educating students for a collective identity in settings where they are learning for and with patients is likely to advance educating for patient‐centred collaborative practice. Abstract : A literature interpretation of 'educating for collaborative practice' has generated questions for reflection. Embracing the tensions inherent in unanswered questions should provide space for communication, initiative and diversity of thought.